Interviewer effects on nonresponse in the European social survey - Annelies G. Blom; Edith D. de Leeuw; Joop J. Hox (University of Essex, Institute for Social and Economic Research (ISER), 2010)
In face-to-face surveys interviewers play a crucial role in making contact with and gaining cooperation from sample units. While some analyses investigate the influence of interviewers on nonresponse, they are typically restricted to single-country studies. However, interviewer training, contacting and cooperation strategies as well as survey climates may differ across countries. Combining call-record data from the European Social Survey (ESS) with data from a detailed interviewer questionnaire on attitudes and doorstep behavior we find systematic country differences in nonresponse processes, which can in part be explained by differences in interviewer characteristics, such as contacting strategies and avowed doorstep behavior.
Keywords: C81; C83; 330; contact; cooperation; interviewer attitudes; doorstep behavior; interviewer questionnaire; paradata; contact data; cross-cultural research; international surveys; Meinungsforschung; Wissenschaftliche Methode; Befragung; EU-Staaten